Application of The Pentahelix Concept in The Iconic Tourism Destination of Kampung Ketupat Samarinda, Indonesia - Habibi, Muhammad; Yani, Ahmad; Eryani, Trisna Waty Riza (Manunggal Halim Jaya, 2025)
Samarinda continues to develop towards its vision as a